Perbedaan Kekuatan Tekan Basis Gigi Tiruan Berbahan Termoplastik Nilon pada Beberapa Ketebalan - Ningsih, Agustini Ria, drg. Noor Hafida Widyastuti, Sp.KG, drg. Nanang Krisnawan (2015)
Thermoplastic nylon base denture is one alternative of denture base materials. The newer of thermoplastic nylon denture base has ability to easily set up, has a biologial suitability and comfortable for patient. One of the mechanical condition of the denture base is having a good compressive strength. Denture base in the manufacturing depends on the thickness and shape anatomy of the alveolar ridge resorption, is not possible with the same thickness. Certain plate thickness can increase the strength of denture base. The objective of this study was to determine the difference in compressive strength of denture base made of thermoplastic nylon in several thicknesses. The samples in this study were 27 specimens who were divided into 3 groups. Beam-shaped samples sized, group 1 (12,5x12,5x25 mm), group 2 (15x15x30 mm), and group 3 (17,5x17,5x35 mm). Measurement of compressive strength thermoplastic nylon was done by using a Universal Testing Machine (UTM). Data was analyzed using One Way ANOVA with a significance level of 0,05. The result showed significant differences among groups with p = 0,006 (p<0,05). The conclusion is that there are the compressive strength differences of denture base made of thermoplastic nylon in several thickness.